A new biomarker neuropeptide Y and bioinformatics analysis of intrahepatic cholestasis of pregnancy. Issue 7 (1st April 2022) - Feng, Fan; Xu, Di; Shao, Yong
Abstract: Aim: To explore the expression of neuropeptide Y (NPY) and bioinformatics characteristics of intrahepatic cholestasis of pregnancy (ICP). Methods: Gene chip data of intrahepatic cholestasis of pregnancy were searched from the GEO database with bioinformatics method, and GSE46157 gene chip was downloaded. Differentially expressed genes in normal pregnant placenta tissue and ICP pregnant placenta tissue (bile acid concentration > 40 μmol/L) were screened by GEO2R. Functional annotation (GO) and pathway analysis (KEGG) were performed with DAVID. STRING online database and Cytoscape software were used for protein interaction network analysis. Maternal serum NPY level of 63 cases of ICP pregnant women and 20 normal pregnant women were investigated by ELISA. Results: After screening 3896 differential genes and protein interaction, the top 14 hub genes were selected with nine up‐regulated and five down‐regulated genes. ICP patients were divided into three subgroups according to serum TBA and ALT levels. Maternal serum NPY levels of pregnant women in ICP subgroups 1, 2, and 3 were significantly higher than those in the normal pregnant women. The number of premature births, meconium‐staining amniotic fluid, neonatal asphyxia, and NICU admission was significantly higher in the ICP subgroup 1 than in the ICP subgroups 2 and 3, and than in the normal pregnant women. Conclusion: This study indicates that many differentially expressed genes and signaling pathways are involved in the pathophysiological procedure of ICP. NPY could be a new biomarker of ICP.